2014
DOI: 10.3390/polym6071877
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Polyelectrolyte Brushes As a Matrix for the Attachment of Gold Nanoparticles: The Effect of Brush Thickness on Particle Distribution

Abstract: The effect of brush thickness on the loading of gold nanoparticles (AuNPs) within stimuli-responsive poly-(N,N-(dimethylamino ethyl) methacrylate) (PDMAEMA) polyelectrolyte brushes is reported. Atom transfer radical polymerization (ATRP) was used to grow polymer brushes via a "grafting from" approach. The brush thickness was tuned by varying the polymerization time. Using a new type of sealed reactor, thick brushes were synthesized. A systematic study was performed by varying a single parameter (brush thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 65 publications
6
51
0
Order By: Relevance
“…In order to apply this equation, one requires estimates of the dry thickness: the water content of the ambient dry brushes (rh = 30%) is ≈2.5% is extracted from ref 30 and was used to calculate the dry thicknesses.…”
Section: Atomic Force Microscopy (Afm) Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to apply this equation, one requires estimates of the dry thickness: the water content of the ambient dry brushes (rh = 30%) is ≈2.5% is extracted from ref 30 and was used to calculate the dry thicknesses.…”
Section: Atomic Force Microscopy (Afm) Measurementsmentioning
confidence: 99%
“…These results are in very good agreement with the work of Christau et al, who investigated the effect of polymer brush thickness on the distribution of the deposited nanoparticles. 30 They concluded that the particle number density increases with brush thickness, which can be attributed to the increased roughness of the thicker brush. The particle number density was calculated using ImageJ.…”
Section: Articlementioning
confidence: 99%
“…Molecules commonly used at this step are organothiols in the case of gold [18][19] or organosilanes for oxidized silicon and glass surfaces [20][21] . More recently, polymer-based coating was applied to attach AuNP on planar substrates [22][23] . Poly(ethylene glycol) (PEG) is particularly adapted to biosensing applications by forming smooth and uniform PEG films that inhibit non specific adsorption [24][25] and provide a high affinity to citrate-stabilized gold nanoparticles [26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…This makes them particularly interesting for controlled release, 7 tunable assembly of coated nanoparticles, 8 responsive nanoactuators 9,10 or for antifouling surfaces. 11,12 More recently, complex systems produced by embedding surfactants, 13,14 gels 15,16 or nanoparticles [17][18][19][20] into polymer brushes have been studied, from which multiresponsive coatings with enlarged applicability as stimuli-responsive systems can be designed. Among them, there are some examples of polyelectrolyte (PE) chains adsorbed onto charged polymer brushes.…”
Section: Introductionmentioning
confidence: 99%